1989
DOI: 10.1111/j.1365-2826.1989.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Activation of Female Sexual Behavior is Accompanied by Hypothalamic Norepinephrine Release

Abstract: The present study employed the intracranial microdialysis technique to measure norepinephrine release in the ventrolateral dendritic fields of the ventromedial hypothalamus of freely-moving animals before and during ovarian steroid (estradiol and progesterone) activation of female sexual behavior (lordosis). One day after implantation of a dialysis probe, animals were injected with 3 ,ug of estradiol benzoate followed 44 h later by 200 pg of progesterone. introduction of a male rat 4 h after progesterone treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 21 publications
3
43
0
Order By: Relevance
“…Changes in VMN NE levels are most likely re lated to induction of lordosis. Vathy and Etgen [10], using in vivo dialysis techniques, found that NE is increased in VMN dialysates from estrogen-and progesterone-treated females who exhibit lordosis. The proestrous amplifica tion of the day/evening increase in NE levels in the MCG suggest that NE in this area may also contribute to induc tion of lordosis.…”
Section: Ne and Lordosismentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in VMN NE levels are most likely re lated to induction of lordosis. Vathy and Etgen [10], using in vivo dialysis techniques, found that NE is increased in VMN dialysates from estrogen-and progesterone-treated females who exhibit lordosis. The proestrous amplifica tion of the day/evening increase in NE levels in the MCG suggest that NE in this area may also contribute to induc tion of lordosis.…”
Section: Ne and Lordosismentioning
confidence: 99%
“…In addition, because of advances in methods for electrochemical measurement of monoamines, catecholamines and some metabolites were also measured in the same microdissected brain regions. Both NE and dopamine have also been linked to some aspects of sexual receptivity [10][11][12][13]. Several studies have already investigated hypothalamic catecholamines during the estrous cycle and on proestrus [14,15], but these stud ies were conducted in relation to catecholaminergic in volvement in the proestrous LH surge.…”
mentioning
confidence: 99%
“…Biol. 109, 1341(1989 DARPP-32, a dopamine-and adenosine 3Ј,5Ј-monophosphate (cAMP)-regulated phosphoprotein (32 kilodaltons in size), is an obligate intermediate in progesterone (P)-facilitated sexual receptivity in female rats and mice. The facilitative effect of P on sexual receptivity in female rats was blocked by antisense oligonucleotides to DARPP-32.…”
mentioning
confidence: 99%
“…In contrast, DAMGO has no effect on KClstimulated NE release in slices from EB-treatcd females. In female rats, estradiol priming is known to be essential for the display of female reproductive behavior, and in a previous microdialysis study, we showed that the display of this behavior in hormone-treated females correlates with increased hypothalamic NE release [18], Thus, it is possible that one of the mechanisms by which estradiol priming facilitates female reproductive behavior is by removing or attenuating tonically active, inhibitory ef fects of endogenous p-opioids on hypothalamic NE re lease. In support of this interpretation is evidence that ovarian steroids facilitate gonadotropin-releasing hor mone secretion by removing the inhibitory influence of endogenous opioid peptides on NE transmission [ 16,20].…”
Section: Discussionmentioning
confidence: 99%
“…There is now a great deal of evidence supporting the hypothesis that estradiol facilitation of female reproduc tive behavior involves enhancement of hypothalamic NE release [18,19]. Neuroendocrine studies also suggest that a major action of estradiol is to decrease the inhibitory influences of endogenous opioid peptides on hypothalam ic NE systems, in part by decreasing hypothalamic (3-endorphin levels [5,[20][21][22][23][24][25][26], Interestingly, our recent work on p-opioid receptor binding demonstrated that gesta tional morphine alters hypothalamic p-opioid receptor density in adult female progeny [27], In ovariectomized (OVX) females, prenatal morphine reduced the density of p-receptor binding sites.…”
Section: Introductionmentioning
confidence: 99%